Oral health status of prison inmates - New South Wales, Australia - Osborn, M.; Butler, Tony; Barnard, P. (Australian Dental Association, 2003)
Background: This paper assesses the oral health status in a prison population and identifies risk factors associated with oral health. Methods: Cross-sectional stratified random sample of 789 prisoners (657 males and 132 females) from 27 correctional centres across New South Wales, stratified by sex, age and aboriginality. A face to face interview was used to collect information on health status and behavioural risk factors. A subset of participants (312 males and 22 females) received an oral examination which enabled the decayed, missing or filled permanent teeth (DMFT) score to be calculated.Results: In the last 12 months 391 (50 per cent) inmates had visited a dentist. Reports on treatment received at this last visit were mainly for dental examinations, (62 per cent), dental fillings, (38 per cent), and dental extractions (28 per cent). Self-reported dental needs indicated that 42 per cent perceived the need for a check-up; the perceived need for dental fillings was highest in females compared with males. The mean DMFT for the population was 20.4 and 3.4 for decayed teeth. Conclusions: This survey demonstrates that the standard of past oral health care for prison inmates is low. There is a need to be more attentive to oral health promotion as eventually respondents will be returning to the community.